Case Report: Diagnosis of cervical carcinoma from pelvic tumor during pregnancy - Hase, E. A.; Cruz, M. C. M.; Kondo, M. M.; Barbosa, M. T. A.; Sadalla, J. C.; Gabrielli, F.; Diz, M. D. P. E.; Siqueira, S. A. C.; Francisco, R. P. V. (Frontiers in Medicine, 2025)
Cervical cancer, the fourth most prevalent cancer in women, is the most common malignant tumor of the female reproductive system and one of the most frequently diagnosed cancers during pregnancy. In Brazil, cervical cancer screening is conducted via Pap smear examination of the cervix, with a false-negative rate ranging between 2 and 50%. Colposcopy is recommended when the Pap smear results reveal abnormalities suggestive of malignancy, and biopsy is reserved for patients who are pregnant only when invasive lesions are suspected. We report the case of a pregnant woman who developed a tumor in the inguinal region, which was biopsied and diagnosed as squamous cell carcinoma. An investigation was performed to identify the primary focus of the tumor. Since the Pap smear was normal, two other potential primary sites were investigated, including the colorectal and bladder regions, which were normal. Despite normal cervical cytopathological examination results and due to the high suspicion of a primary cervical focus, additional diagnostic evaluations were performed, which confirmed cervical squamous cell carcinoma as the primary site. We described this case due to the lack of similar reports in the literature of cervical cancer diagnosed in pregnant or non-pregnant patients with normal oncotic Pap smears, initially diagnosed by biopsy of an inguinal tumor, and to highlight the importance of complementing the diagnostic process with colposcopy in patients with a high clinical suspicion of cervical cancer, even in cases of negative Pap smear results.